A contribution for the understanding of load-transfer mechanisms in multi-leaf masonry walls : testing and modelling - Binda, L. (2006)
Predicting the behaviour of multiple-leaf masonry walls is a challenging issue, given the influence of a wide range of factors as the mechanical properties of the leaves, the leaves dimensions and the way the leaves are connected to each other. In the present paper, novel experimental results in large three-leaf wallets subjected to shear and compression are introduced together with a careful numerical interpretation. Two types of collar joints (with and without shear keys) and two types of stone (weak limestone and strong sandstone) are considered in the tests. The influence of the boundary conditions on the numerical response is thoroughly investigated and good agreement with the experimental results is found. Moreover, a discussion on simplified calculations for practical assessment of existing walls is addressed.